Contribuições da organização da gestão escolar para a ressignificação do espaço público da escola - Miranda, Natália Pergher (2011)
This Master Thesis presents some contributions from school management organization for the redefinition of school s public space, considering the market assumption which spreads the current economic interests that are directly focused on the organization of education in order to democratization processes through the globalized educational reforms and, in this way, reducing the places of collective actions. The question research that guides this study was: how the school management organization could contribute with the redefinition of the school s public space? To answer this research request, I present as a main goal of the study: to comprehend how the school management organization based on democratic principles could contribute to the redefinition of the school public space? From this, these are the specific goals: (a) to comprehend the formation processes of school public spaces through the analysis of political, social, historical and economical contexts; (b) analyzing and discussing on democratic management organization through legal references, also according to theoretical and conceptual aspects and the results of the research developed with the School Council s participants of a public school in the state of Rio Grande do Sul in Santa Maria city; (c) redefining the school management organization concepts in order to enhance them as possibilities for the public space of school. The methodology is based on the references of qualitative researches in Education that was written by Minayo (2003), Santos Filho (1995) and Triviños (2008). To the data collection, it was used the reflective interview, proposed by Szymanski (2008), with participants of School Council of a public school in the state of Rio Grande do Sul in Santa Maria city. To work with the data collected during the interviews, it was used the Content Analysis according to Bardin (1977; 2010). The theoretical reference was composed by legal documents that set democratic management in public education like the Brazilian Constitution (1988), the law of Democratic Management to Public Education in the State of Rio Grande do Sul (1995), the Educational Directive Law related to Brazilian Education (1996) and by authors that write about this theme and assist in the conceptual elaboration about the school management democratization: Cambi (2000), Beltrán (2000), Wood (2003), Libâneo (2003; 2006; 2008), Dagnino (2004), Arendt (2007), Paro (2010). As a relevant contribution of school management organization to the public school space, it may infer the School Councils action as an important place to discussion and conflicts exposure, as a part composed by the collective of school through the representation of each section of the community. Still, it s in this building context of collective practices made in a democratic way that the traditional approach of bourgeois dominance reveals its weakness, offering more possibilities to open new practices that bring new meanings to school institutions. This result, therefore, confirms that the collective could exercise power to changing structures in which they are inserted and, through this effective and collective encircling force, it could be possible to reassess the public spaces in a collective and democratic way, including the school space.